Legal Framework for the Role of Village Officials in Preserving Local Cultural Wisdom Values: Study of Nagori Tongah, Purba District, Simalungun Regency)(Study of Nagori Tongah, Purba District, Simalungun Regency - Jadelmar Purba; Bambang Fitrianto; Siti Nurhayati (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
There are various obstacles and constraints in preserving local culture, one of which is the lack of maximum community involvement and limited supporting infrastructure. This study aims to examine in depth the legal basis of the Nagori Tongah Village apparatus in preserving local culture, as well as to comprehensively discuss the obstacles faced by the Nagori Tongah Village apparatus in preserving local culture and the policies to address them. The type of research used is normative legal with a descriptive-analytical approach, discussing existing legal phenomena and issues and testing them based on laws and regulations as well as legal norms. The results of this study show that the legal basis for the Nagori Tongah Village Administration in preserving local culture is regulated in several regulations, ranging from the 1945 Constitution, laws, government regulations, to local/village government regulations. The obstacles faced by the Village Administration in its efforts to preserve local culture are: changes in social values and technology, economic modernization, minimal community participation, and limited resources and supporting infrastructure. To overcome these obstacles, policies have been implemented, including cultural preservation planning and structuring, fund/budget allocation, and cooperation with relevant parties in cultural promotion